Narrowing the Gap between Research and Practice Some Suggestions for Vietnam - Thanh, Le Trung; Ha, Nguyen Thi Hai (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
An important objective of any research is to create guiding evidence or to propose improvements and/or solutions for practice. In order to apply proven research results, institutions, organizations and individuals should review appropriately relevant topics to better understand the researched issues, select information for the decision-making process, and identify solutions for each specific situation. Although research is very important, there is a large gap between the research results and the practical applications in Vietnam that makes the widespread application of research evidence into practice difficult. On the basis of synthesizing and evaluating research documents worldwide, as well as analyzing the real situations of the research/application gap, the paper examines the origins and causes for the existence of this gap. Some suggestions to narrow the gap are raised for Vietnam.